Два брата: [сказки : для младшего школьного возраста] / Евгений Шварц ; худож. Д. Махашвили, Ю. Панипартова - Шварц Евгений Львович (Библиотека школьника, 2001)
Экземпляры: ф.16 (2002) / Инвентарный номер: 43783 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Ш 33 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-4